Absorbed Radiation Dose in Radiosensitive Organs Using 64- and 320-Row Multidetector Computed Tomography: A Comparative Study. (6th August 2014) - Khan, Atif N.; Shuaib, Waqas; Nikolic, Boris; Khan, Mohammad K.; Kang, Jian; Khosa, Faisal
Abstract : Aim . To determine absorbed radiation dose (ARD) in radiosensitive organs during prospective and full phase dose modulation using ECG-gated MDCTA scanner under 64- and 320-row detector modes. Methods . Female phantom was used to measure organ radiation dose. Five DP-3 radiation detectors were used to measure ARD to lungs, breast, and thyroid using the Aquilion ONE scanner in 64- and 320-row modes using both prospective and dose modulation in full phase acquisition. Five measurements were made using three tube voltages: 100, 120, and 135 kVp at 400 mA at heart rate (HR) of 60 and 75 bpm for each protocol. Mean acquisition was recorded in milligrays (mGy). Results . Mean ARD was less for 320-row versus 64-row mode for each imaging protocol. Prospective EKG-gated imaging protocol resulted in a statistically lower ARD using 320-row versus 64-row modes for midbreast (6.728 versus 19.687 mGy, P < 0.001 ), lung (6.102 versus 21.841 mGy, P < 0.001 ), and thyroid gland (0.208 versus 0.913 mGy;P < 0.001 ). Retrospective imaging using 320- versus 64-row modes showed lower ARD for midbreast (10.839 versus 43.169 mGy, P < 0.001 ), lung (8.848 versus 47.877 mGy, P < 0.001 ), and thyroid gland (0.057 versus 2.091 mGy;P < 0.001 ). ARD reduction was observed at lower kVp and heart rate. Conclusions . Dose reduction to radiosensitive organs is achieved using 320-row compared to 64-row modes for both prospective and retrospective gating, whereas 64-row mode is equivalent to the same model 64-row MDCT scanner.